The Structure and Chemical Composition of Wall Paintings From Islamic and Christian Times in the Seville Alcazar. (3rd November 2015) - Robador, M. D.; De Viguerie, L.; Pérez‐Rodríguez, J. L.; Rousselière, H.; Walter, P.; Castaing, J.
Abstract : Wall paintings from the Islamic epoch (10th to 12th centuries) and the Christian monarchy (14th to 16th centuries) have been recovered in discarded materials and on walls after reconstruction works in the Seville Alcazar. These paintings have spent centuries underground or under a plaster coat. Portable X‐ray fluorescence (XRF) and combined XRF/X‐ray diffraction (XRD) were employed in situ, as well as scanning electron microscopy (SEM–EDX), grazing angle incidence XRD and micro‐Raman spectroscopy, on cross‐section samples to fully characterize the materials in the wall paintings. Using these methods, the fresco technique was demonstrated, and many kinds of pigments were identified in accordance with the various periods of the history of the Alcazar, thus assessing the authenticity of all the wall paintings studied here.